2018
DOI: 10.2166/wpt.2018.028
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum sewerage systems – a solution for fast growing cities in developing countries?

Abstract: Developed more than a century ago, the potential of vacuum sewerage systems remains underexploited. At the same time, the rapid urbanization in Asia brings about major challenges for municipal utilities. In this context, the GIZ (Deutsche Gesellschaft fuer Internationale Zusammenarbeit) project ‘Integrated Resource Management in Asian Cities: the Urban Nexus’ gives technical advice to stakeholders in the partner cities. Fraunhofer IGB, having operated a vacuum sewer system for more than ten years in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The ratio of capital intensity of pressure sewer construction for a 150-m pipeline in dry soils is twice that of gravity sewers. For severely irrigated soils, the differences are even more pronounced [ 30 , 31 , 32 , 33 , 34 ]. Studies on the dynamics of sewage inflow to gravity sewer systems indicated a large infiltration of rainwater into the sewer system.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of capital intensity of pressure sewer construction for a 150-m pipeline in dry soils is twice that of gravity sewers. For severely irrigated soils, the differences are even more pronounced [ 30 , 31 , 32 , 33 , 34 ]. Studies on the dynamics of sewage inflow to gravity sewer systems indicated a large infiltration of rainwater into the sewer system.…”
Section: Discussionmentioning
confidence: 99%